Environmental Enrichment, Age, and PPARα Interact to Regulate Proliferation in Neurogenic Niches - Pérez-Martín, Margarita; Rivera, Patricia; Blanco, Eduardo; Lorefice, Clara; Decara, Juan; Pavón, Francisco J.; Serrano, Antonia; Rodríguez de Fonseca, Fernando; Suárez, Juan (Frontiers in Neuroscience, 2016)
Peroxisome proliferator-activated receptor alpha (PPARα) ligands have been shown to modulate recovery after brain insults such as ischemia and irradiation by enhancing neurogenesis. In the present study, we investigated the effect of the genetic deletion of PPARα receptors on the proliferative rate of neural precursor cells (NPC) in the adult brain. The study was performed in aged Pparα-/- mice exposed to nutritional (treats) and environmental (games) enrichments for 20 days. We performed immunohistochemical analyses of cells containing the replicating cell DNA marker 5-bromo-2’-deoxyuridine (BrdU+) and the immature neuronal marker doublecortin (Dcx+) in the main neurogenic zones of the adult brain: subgranular zone of dentate gyrus (SGZ), subventricular zone of lateral ventricles (SVZ) and/or hypothalamus. Results indicated a reduction in the number of BrdU+ cells in the neurogenic zones analyzed as well as Dcx+ cells in the SGZ during aging (2, 6, 18 months). Pparα deficiency alleviated the age-related reduction of NPC proliferation (BrdU+ cells) in the SVZ of the 18-months-old mice. While no genotype effect on NPC proliferation was detected in the SGZ during aging, an accentuated reduction in the number of Dcx+ cells was observed in the SGZ of the 6-months-old Pparα-/- mice. Exposing the 18-months-old mice to nutritional and environmental enrichments reversed the Pparα-/--induced impairment of NPC proliferation in the neurogenic zones analyzed. The enriched environment did not modify the number of SGZ Dcx+ cells in the 18 months old Pparα-/- mice. These results identify PPARα receptors as a potential target to counteract the naturally observed decline in adult NPC proliferation associated with aging and impoverished environments.